Molecular-genetic characterization of Ukrainian patients with mucopolysaccharidosis IIIA: identification of three new mutations in the heparan-N-sulfatase gene - Trofimova, N.S.; Olkhovich, N.V.; Gorovenko, N.G. (Вiopolymers and Cell, 2016)
Mucopolysaccharidosis type III or Sanfilippo syndrome (MIM # 252900) is a rare hereditary autosomal-recessive metabolic disorder, which occurs due to the deficiency of heparan-N-sulfatase enzyme (EC 3.10.1.1). Aim. To identify the whole spectrum of mutations in SGSH gene in Ukrainian patients with MPS III A. Methods. RFLP-analysis, SSCP method, sequencing. Results. We have identified 100 % (42/42) mutant alleles of SGSH gene in 23 patients (two probands had siblings with identical genotypes) with MPS III A from 21 Ukrainian family. The range of mutations in SGSH gene in Ukrainian patients with MPS III A is represented with 7 known missence-mutations , R74C, R245H, T271M, E292K, S298P, E369K, N389K and 2 single nucleotide deletions, c.1080delC and c.1135delG. We identified three new mutations in the SGSH gene: a missence-mutation G149R,a deletion c.216delC, and a deletion of 27 bp TCC^348CTCctgccggcgctggaggccgagcccctcTGGGCCACC. Conclusions. The data obtained may be useful for molecular-genetic analysis of Ukrainian patients with MPS III A.